2020
DOI: 10.1111/cobi.13608
|View full text |Cite
|
Sign up to set email alerts
|

Let's welcome a variety of voices to invasion biology

Abstract: Article Impact Statement: Efforts by some invasion biologists to limit voices from the humanities and social sciences weaken the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…As conservation decision-makers need multi-threat assessments such as ours to develop the most effective conservation actions [56], we use this well-researched case study as a model for informing conservation decisions of other threatened plant taxa [16]. Our report is useful for discussing the Anthropocene consequences and how the global disciplines of conservation science and invasion biology can be studied at the local level [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In the short term, mitigation of the phytophagous non-native species' damage remains the only acute need to conserve this unique gymnosperm tree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As conservation decision-makers need multi-threat assessments such as ours to develop the most effective conservation actions [56], we use this well-researched case study as a model for informing conservation decisions of other threatened plant taxa [16]. Our report is useful for discussing the Anthropocene consequences and how the global disciplines of conservation science and invasion biology can be studied at the local level [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In the short term, mitigation of the phytophagous non-native species' damage remains the only acute need to conserve this unique gymnosperm tree.…”
Section: Discussionmentioning
confidence: 99%
“…Although this would appear to increase biodiversity, the negative impact of the new invasions on native organisms may actually decrease biodiversity [6]; therefore, due to the global influence of non-native organisms on native biodiversity, invasion biology has emerged as a bona fide discipline [10][11][12]. As this discipline continues to develop, the need to include multiple stakeholder groups such as humanities and social sciences has been recognized as a means of enabling successful outcomes [13]. Eradication of non-native species is most successful if organized efforts are initiated early in the invasion process.…”
Section: Introductionmentioning
confidence: 99%
“…Some are of enormous economic importance to the well-being of people, and researchers in the humanities and social sciences are participating in discussions on this aspect of the issue. Among them, Davis (2020) emphasizes that several factors are creating ecologically novel environments and calls for the presence of different perspectives and voices. Vaz et al (2017) analyzed interdisciplinarity in invasion science papers and found that 92.4 % of publications with interdisciplinary participation deal with ecological questions, and only 4.4 and 3.2 % on social and social-ecological questions, respectively.…”
Section: Importance Of Invasive Species In Restorationmentioning
confidence: 99%
“…Some species can establish and spread in a novel environment more successfully than others, and defining what makes a species 'invasive' is hotly contested [1][2][3][4] . Invasion biologists continue to debate whether an invasion's success can be better attributed to an intrinsic property of the founding population or to extrinsic conditions experienced by the population.…”
Section: Introductionmentioning
confidence: 99%